The effectiveness of platelet concentrations in periodontal surgeries - Al-Azem, Ronad; Ali, Neveen; Mostafa, Diana (International Journal of Dental Research, 2018)
Platelets release several growth factors which stimulate tissue regeneration. Several techniques for platelet concentrates such as platelet rich plasma (PRP), plasma rich in growth factors (PRGF), platelet rich fibrin (PRF) and concentrated growth factors (CGF) have been introduced in dental surgeries for the prevention of hemorrhage and acceleration of tissue regeneration. However, a fabricating growth factors-enriched bone graft matrix which is called â€œsticky boneâ€ has been demonstrated to provide stabilization in bony defects. In this article, we presented the method of preparing and utilizing CGF and sticky bone and evaluate the effect of CGF mixed with bone graft and CGF barrier membrane in periodontal surgeries.Methodology: We used websites such as PubMed, Scopus, and ISI Web of knowledge to get related articles about this subject. The research process involved specific key words " concentrated growth factorâ€- â€œPlatelet rich fibrinâ€- growth factors-enriched bone graftâ€ - â€œsticky boneâ€ to find more articles which published from 2007 to March 2018.Results: We reviewed 48 articles, 43 articles were excluded. Only five articles have been conducted. Original human studies and case report were included.Conclusion: We concluded that the use of sticky bone and CGF is effective in bone grafting and implant.Â Â